2021
DOI: 10.1037/pspi0000259
|View full text |Cite
|
Sign up to set email alerts
|

Meta-humanization reduces prejudice, even under high intergroup threat.

Abstract: Meta-dehumanization, the perception your group has been given less than human qualities, contributes to a vicious cycle of outgroup dehumanization and hostility, such as, hate crimes and support for discriminatory policies. Minimal research has investigated potential benefits of meta-humanization, or perceiving your group has been given dignified qualities. Across seven studies (N = 1,261) in Canada and the United Kingdom, we focus on Muslimnon-Muslim relations and provide the first empirical evidence to sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The same is true of dehumanization: American political partisans think members of the other party dehumanize them nearly three times more than is actually the case [62,63]. Fortunately, meta-dehumanization appears to be corrigible: informing non-Muslim Westerners that Muslims in the Middle East consider them fully human reduces their blatant dehumanization of Muslims [104,107], particularly among those who perceive Muslims to be most threatening at baseline [107]. Other work in Kosovo and North Macedonia showed that participants told an outgroup considered their own group fully human were more likely to empathize with and accept the help of an outgroup member [108].…”
Section: Theoretical Challenges To Dehumanization Researchmentioning
confidence: 99%
“…The same is true of dehumanization: American political partisans think members of the other party dehumanize them nearly three times more than is actually the case [62,63]. Fortunately, meta-dehumanization appears to be corrigible: informing non-Muslim Westerners that Muslims in the Middle East consider them fully human reduces their blatant dehumanization of Muslims [104,107], particularly among those who perceive Muslims to be most threatening at baseline [107]. Other work in Kosovo and North Macedonia showed that participants told an outgroup considered their own group fully human were more likely to empathize with and accept the help of an outgroup member [108].…”
Section: Theoretical Challenges To Dehumanization Researchmentioning
confidence: 99%
“…For example, in the aforementioned studies (Ramsey et al, 2017; Ramsey & Hoyt, 2015), women were asked to evaluate the extent to which their partner surveyed their bodies and tested the relationship of such perceptions with women's self‐objectification. On the one hand, meta‐perceptions are important indicators of one's attitudes and behaviours (e.g., Grutterink & Meister, 2021; Pavetich & Stathi, 2021); on the other hand, however, they are likely affected by a priori attitudes toward their partner, cognitive biases or self‐enhancement motives (e.g., Sedikides & Gregg, 2008) and, thus, they cannot be considered as a fully reliable indicator of partner's tendency to objectify.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated a relationship between control, prejudice, and threat (Greenaway et al, 2014), threat and dehumanization (Haslam & Loughana, 2014), and meta‐dehumanization, dehumanization, and hostility (Kteily & Bruneau, 2017; Pavetich & Stathi, 2020). The current research drew from these topics to theoretically extend the limited literature investigating antecedents and outcomes of meta‐dehumanization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research demonstrated that those who dehumanize are more likely to support aggressive policies, and those who are dehumanized are in turn more likely to act in aggressive ways that perpetuate the existing dehumanizing views (Kteily et al, 2016; Pavetich & Stathi, 2020). In line with this, the rise of uncertainty, aggressive political discourse, and negative stereotypes revolving around Muslims creates an atmosphere of hostility for intergroup relations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation